Studi Kuat Geser Tanah Timbunan Yang Dipadatkan Dengan Cara Kompaksi Statik dan Kompaksi Dinamik Pada Tanah Vulkanik - Susanto, Supardi Tri; Rahardjo, Paulus. P.; Karlinasari, Rinda (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2024)
Compaction is essential in achieving the desired density of fill materials in accordance with technical specifications. There are existing differences in the compaction methods employed in the field and at laboratory testing, with in field using rolling compaction, while the laboratory employs pounding compaction. The objective of this study is to compare static and dynamic laboratory compaction methods and their effects on shear strength. Shear strength testing is conducted using the Triaxial Unconsolidated Undrained (TX-UU) approach. The research findings show that in laboratory compaction of low plasticity silt (ML) samples, there is a dry unit weight difference of 2.90%, and for high plasticity silt (MH) samples, a dry unit weight difference of 3.42% is observed when switching from dynamic compaction to static compaction. Additionally, the shear strength values for ML and MH samples increase by 10.37% and 13.63%, respectively, when switching from dynamic to static compaction. These results demonstrate that compaction energy and shear strength are positively correlated.